Modelo de Equilibrio General Aplicado Tributario - Ramírez Álvarez , José Fernando (2007)
Evasion is one of the most concerning and distorting factors for the government on tax collection; that is why its searching and the analysis of their possible causes and consequences has been motivated within the economic system. In Ecuador, despite of the considerable effort of tributary authority for increasing and/or expanding its field and control, this factor has always pointed out the difference in collection and questioned the efficiency of the process used for increasing it. At this line, the present paper exhibits the development of Tributary Applied General Equilibrium Model (MEGAT) for the counterfactual analysis of a wide set of tributary policies, that includes the evasion behavior in the collection of Add-Valorem-Tax (IVA) and Income-Tax (IRC). In deed, we adopt some particular ideas from A-S model in the direct tax payment and the perspective of Marrelli in the indirect tax payment. On the other hand, the fundamental structure for the equilibrium system, as well as the Social Accounting Matrix, is taken from de Applied Ecuadorian General Equilibrium Model (MEEGA), and updated to the most recent economic environment 2004.